(untitled) (Research, Society and Development, 2020)
This article aims to expand the reflections on the teaching of nurses in palliative oncology care from the perspective of the concepts of institution, instituted and instituting Institutional Analysis, considering nursing education as an institution in constant movement and being crossed by other institutions. The research is bibliographic, exploratory and with a qualitative approach, using the theoretical-methodological framework of Institutional Analysis and its concepts of institution, instituted and instituting. The bibliographic survey was carried out in two stages: the first carried out on the Virtual Health Library portal and the second on official documents that address palliative care, which made it possible to expand the discussion on the theme. The results highlight the need for changes in the training of nurses, recognizing that the consolidation of new practices brought about by palliative care constitutes a challenge in the instituted training scenarios, either in the training centers or in the services. It also brings the reflection that instituting processes, such as the nursing practice in palliative care, produce strangeness and ruptures, having as a positive aspect the provocation of changes and expansion of the possibilities of training centers and services to carry out new experiments, problematizing the context where are inserted. It concludes considering that every instituting process must indicate movements of change that lead to new paths, thought by a collective, where professionals and students must perceive themselves as protagonists of this process of building new practices in nursing care.